Narrative Review of Internet-Based Self-Help Tools for Body-Focused Repetitive Behaviors: Recommendations for Clinical Practice - Emi M. Murase; Sawye Raygani; Jenny E. Murase (Dermatology and Therapy)
Abstract Introduction Body-focused repetitive behaviors (BFRBs), such as skin-picking, hair-pulling, and nail-biting, impair quality of life (QOL). While habit reversal training (HRT) is effective, access is often limited. Internet-based self-help interventions offer an alternative, improving accessibility for patients unable to attend in-person therapy. Methods We reviewed randomized controlled trials analyzing self-help or internet-based interventions for BFRBs in adults. PubMed searches yielded 1033 studies, 12 of which met the inclusion criteria, focusing on self-guided interventions for various BFRBs. Results The review found that the “Free from BFRB” website was the most studied resource and consistently had high patient satisfaction. Self-guided HRT, decoupling, and decoupling in-sensu consistently reduced symptoms and improved QOL. Decoupling techniques were especially effective for trichotillomania and nail-biting. Discussion Internet-based self-help interventions, especially self-help HRT, decoupling, and decoupling in-sensu, offer effective and accessible treatment options for managing BFRBs, particularly for those facing barriers to traditional therapy such as stigma, cost, or location. Engagement and frequency of use are important for the efficacy of self-help options, and therapist-guided treatments may offer more personalized, comprehensive care.